Hak Kebebasan Beragama: Analisis Hadis Perang Perspektif Hermeneutika Gadamer - Ihsanuddin, Nurul (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
This article talks about the right to freedom of religion in Islam, especially the right to freedom of religion expressed in the hadith nabawi. The hadith studied in this paper is a hadith of war, a hadith that seems to contain imperative and provocative messages for Muslims to fight against people until they declare the creed. There are many studies that examine religious freedom in Islam, only those studies are more general and do not specifically address specific hadiths. In general, this paper seeks to answer the question of how the hadith nabawi views religious freedom? And how to understand +the hadith of war, a hadith that seems to call for war in spreading Islam? To answer that question, the author will examine the hadith of war with the help of Hans-Georg Gadamer's hermeneutic approach which includes Historically Effected Consciousness, Pre-understanding, Fusion of Horizons, and Application. The use of this hermeneutical approach as an effort to manifest integration and interconnection of general and religious scholarship. Because science is a light that there is no dichotomy in the middle. With the use of this hermeneutical approach the author wishes to avoid as much as possible from the hole of objectivity of understanding.